Impact of Early Fluid Balance on 1-Year Mortality in Critically Ill Patients With Cancer: A Retrospective Study in Central Taiwan. (20th August 2020) - Chen, Yung-Chun; Zheng, Zhe-Rong; Wang, Chen-Yu; Chao, Wen-Cheng
A positive fluid balance has been found to be deleterious in critically ill patients; however, the impact of early fluid balance, particularly on long-term outcomes, in critically ill patients with cancer remains unclear. We performed this retrospective study at a tertiary-care referral hospital with 1500 beds and 6 intensive care units (ICUs) in central Taiwan, and 942 patients with cancer admitted to ICUs during 2013 to 2016 were enrolled. The primary outcome was 1-year mortality. Cancer-related data were obtained from the cancer registry, and data during ICU admissions were retrieved from the electronic medical records. The association between fluid balance, which was represented by median and interquartile range, and 1-year mortality was determined by calculating the hazard ratio (HR) with 95% confidence interval (CI) using a multivariable Cox proportional hazards regression model. The in-hospital mortality rate was 22.9% (216 of 942), and the mortality within 1 year after the index ICU admission was 38.7% (365 of 942). Compared to survivors, nonsurvivors tended to have a higher Acute Physiology and Chronic Health Evaluation II score (24.1 ± 6.9 vs 20.5 ± 6.2, P < .01), a higher age (65.0 ± 14.4 vs 61.3 ± 14.3, P < .01), a higher serum creatinine (1.5 ± 1.3 vs 1.0 ± 1.0, P < .01), and a higher cumulative day 1 to 4 fluid balance (2669, 955-5005 vs 4103, 1268-7215 mL, P < .01). Multivariable Cox proportional hazards regression analysis found that cumulative day-4 fluid balance was independently associated with 1-year mortality (adj HR 1.227, 95% CI: 1.132-1.329). A positive day 1 to 4 cumulative fluid balance was associated with shorter 1-year survival in critically ill patients with cancer. Further studies are needed to validate this association.